2020
DOI: 10.1021/acssuschemeng.9b06156
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Microalgal Harvesting Using Microalgae-Derived Extracellular Polymeric Substance as Flocculation Aid

Abstract: Coagulation-based harvesting has been widely used in microalgal biomass harvesting. However, the coagulant contamination in the harvested biomass may negatively affect the applications in feedstock processing for food, feed, and fuel. In this study, extracellular polymeric substances (EPSs) were derived from microalgae, Scenedesmus acuminatus, and then used as a bioflocculant to aid the flocculation of the same algae. The results show that the alum coagulant (Al3+) usage was significantly reduced from 77.6 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…EPS produced by Scenedesmus acuminatus are used for the flocculation of the same microalgae and the harvesting efficiency > 80%. Low molecular weight EPS composed of mannose and glucose influences the microalgal biomass harvesting process (Yang et al 2020 ). Detailed bio-flocculation techniques and their flocculation mechanisms are discussed in a review reported by Ummalyma et al ( 2017 ).…”
Section: Biorefinery Of Food Industry Wastewater For Production Of Va...mentioning
confidence: 99%
“…EPS produced by Scenedesmus acuminatus are used for the flocculation of the same microalgae and the harvesting efficiency > 80%. Low molecular weight EPS composed of mannose and glucose influences the microalgal biomass harvesting process (Yang et al 2020 ). Detailed bio-flocculation techniques and their flocculation mechanisms are discussed in a review reported by Ummalyma et al ( 2017 ).…”
Section: Biorefinery Of Food Industry Wastewater For Production Of Va...mentioning
confidence: 99%
“…This process was demonstrated by Guo et al [7], using supernatant and cell suspension from the autoflocculating Scenedesmus obliquus AS-6-1 culture for the recovery of non-flocculating microalgae biomass. Furthermore, to increase the efficiency of bioflocculation processes, other flocculants such as Al 3+ and Fe 3+ can be added together with extracellular polysaccharides [7,10,76]. According to Yang et al [76], the extracellular polymeric substance co-extracted in the Al 3+ recovery process after the primary flocculation step contributed to the clotting process of Scenedesmus acuminatus.…”
Section: Bioflocculationmentioning
confidence: 99%
“…In this sense, Yang et al [10] reported bioflocculant activity of EPS from Scenedesmus acuminatus in the recovery of the biomass of this same microalga. The results showed that the addition of microalgae EPS (3.2 mg g −1 ) significantly reduced the use of aluminum coagulant (Al 3+ ) from 77.6 to 4.5 mg g −1 .…”
Section: Introductionmentioning
confidence: 97%
“…Several microalgae could release various polysaccharides, also known as exopolysaccharides (EPS), into the growth media [59]. Negatively charged groups within EPS molecules are also capable of absorbing metals [60]. Both living and dead cells of microalgal are capable of metal removal, although the metal removal efficiencies for living cells are higher compared to dead cells [61].…”
Section: Metals Adsorption/uptakementioning
confidence: 99%